REVEALING NETIZENS' RESPONSES TO THE WITHDRAWAL OF DANGEROUS PRODUCTS: A CASE STUDY OF PINKFLASH COSMETICS - Annisa Tri Septiani; Irwansyah Irwansyah (Program Pascasarjana UIN Sumatera Utara, 2026)
The revocation of the distribution permits for two Pinkflash products by the Food and Drug Monitoring Agency (BPOM) not only triggered a reputational crisis on social media but also revealed how the digital public assesses brand responsibility in regulatory crises related to product safety. This study aims to analyze netizen responses to Pinkflash's clarification and interpret the brand's crisis communication patterns through the perspective of Situational Crisis Communication Theory (SCCT). Academically, this study offers novelty by utilizing netizen comments as the primary data for understanding public acceptance of brand response strategies in the context of a cosmetics crisis triggered by regulatory intervention. The study used a descriptive qualitative approach with a qualitative content analysis of Pinkflash's official clarification post and netizen comments on social media. The results show that netizen responses are divided into support, criticism, distrust, and concern over product safety. Clarification and apology are considered important initial steps, but are not sufficient to restore trust. These findings confirm that the effectiveness of digital crisis communication is determined not only by the transparency of the message but also by the consistency of post-crisis corrective actions.